2022
DOI: 10.1002/jcp.30919
|View full text |Cite
|
Sign up to set email alerts
|

IGF2BP2, an RNA‐binding protein regulates cell proliferation and osteogenic differentiation by stabilizing SRF mRNA

Abstract: Osteoblast proliferation and osteogenic differentiation (OGD) are regulated by complex mechanisms. The roles in cell proliferation and OGD of RNA-binding proteins in the insulin-like growth factor 2 mRNA-binding protein (IGF2BP) family remain unclear. To elucidate this, we examined the differential expression of IGF2BP2 in OGD and osteoporosis, and the expression profile of IGF2BP2-binding RNA in vitro. We screened the GEO database for differential expression of IGF2BP in OGD and osteoporosis, and verified the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Zhang et al [ 49 ] found that IGF2BP2 targets and stabilizes serum response factor ( SRF ) mRNA, regulates osteogenic differentiation (OGD), and can be a potential marker and therapeutic target for osteoporosis and OGD. Although the role of IGF2BP2 in cancer has been extensively studied, the mechanism by which it regulates cell proliferation and differentiation remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al [ 49 ] found that IGF2BP2 targets and stabilizes serum response factor ( SRF ) mRNA, regulates osteogenic differentiation (OGD), and can be a potential marker and therapeutic target for osteoporosis and OGD. Although the role of IGF2BP2 in cancer has been extensively studied, the mechanism by which it regulates cell proliferation and differentiation remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Insulin-like growth factor 2 mRNA-binding protein 2 (IGF2BP2), an RNA-binding protein (RBP), plays an important role in cell growth and human disease progression [ 8 , 9 ]. As an N6-methyladenosine (m6A) reader, IGF2BP2 is involved in cancer progression by binding to different RNAs [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%